Fluxo de CO2 em cultivo da palma de óleo com híbridos interespecíficos (Elaeis guineensis Jacq x Elaeis oleifera (Kunth) Cortés) no Leste da Amazônia - FONSECA, Luiz Carlos Neves da (Universidade Federal do Pará, 2018)
Terrestrial ecosystems are important for the CO2 exchange between surface and atmosphere. The objective of this paper was to characterize the daily and seasonal variation of CO2 flux in oil palm cultivation with interspecific hybrid (Elaeis guineensis Jacq. x Elaeis oleifera (Kunth) Cortés) in eastern Amazonia. The study was carried out at Marborges Agroindústria S.A., Moju - Pará, where a micrometeorological tower was installed to obtain meteorological and CO2 data from January to December of 2015. The wet season (1.974 mm) covered the months of January-June and December (P > 150 mm month-1) and the dry season (345 mm) included the months of July-November (P < 150 mm month-1). The average daily values of CO2 concentration [CO2] were lower and average night values were higher, mainly at levels below the canopy (5.8; 2.1; 0.5 m). The average daily values of CO2 uptake peaked at noon, with 22.3 (± 0.98) μmol m-2 s-1 in the wet season and 21.0 (± 0.47) μmol m-2 s-1 in the dry season. There was little nocturnal variation in the average values of CO2 emission, 5 (± 0.20) μmol m-2 s-1, in wet and dry seasons, by oil palm cultivation with interspecific hybrid. Generally, the daily CO2 exchange cycle presented a slight difference between the wet and dry season, even in drought year in eastern Amazonia.